Dual targeting of tumour cells and host endothelial cells by novel microtubule-targeting agents, pyrrolo-1,5-benzoxazepines. - LAWLER, MARK; WILLIAMS, DAVID CLIVE; NATHWANI, SEEMA; MEEGAN, MARY JANE; ZISTERER, DANIELA MARIA (Springer, 2010)
Advanced hormone-refractory prostate cancer is associated with poor prognosis and limited treatment options. Members of the pyrrolo-1,5-benzoxazepine (PBOX) family of compounds exhibit anti-cancer properties in cancer cell lines (including multi-drug resistant cells), ex vivo patient samples and in vivo mouse tumour models with minimal toxicity to normal cells. Recently, they have also been found to possess anti-angiogenic properties in vitro. However, both the apoptotic pathways and the overall extent of the apoptotic response induced by PBOX compounds tends to be cell-type specific. Since the effect of the PBOX compounds on prostate cancer has not yet been elucidated, the purpose of this study was to investigate if PBOX compounds induce anti-proliferative effects on hormone-refractory prostate cancer cells. We examined the effect of two representative PBOX compounds, PBOX-6 and PBOX-15, on the androgen-independent human prostate adenocarcinoma cell line, PC3. PBOX-6 and -15 displayed anti-proliferative effects on PC3 cells, mediated initially through a sustained G2/M arrest. G2/M arrest, illustrated as DNA tetraploidy, was accompanied by microtubule depolymerisation and phosphorylation of anti-apoptotic proteins Bcl-2 and Bcl-xL and the mitotic spindle checkpoint protein BubR1. Phosphorylation of BubR1 is indicative of an active mitotic checkpoint and results in maintenance of cell cycle arrest. G2/M arrest was followed by apoptosis illustrated by DNA hypoploidy and PARP cleavage and was accompanied by degradation of BubR1, Bcl-2 and Bcl-xL. Furthermore, sequential treatment with the CDK1-inhibitor, flavopiridol, synergistically enhanced PBOX-induced apoptosis. In summary, this in vitro study indicates that PBOX compounds may be useful alone or in combination with other agents in the treatment of hormone-refractory prostate cancer.
PUBLISHED
Keywords: Biochemistry; Oncology; PBOX; microtubule-targeting agents; flavopiridol; prostate cancer